Study effect of IL-35 and some sex hormones in male patients who have multiple sclerosis (MS) - Bidan, Ali K.; A. Hamzah, Nisreen (International Journal of Advanced Chemistry, 2015)
Multiple sclerosis (MS) is a disease characterized by inflammation and demyelination. Currently, the cause of MS is unknown. An early and accurate diagnosis of multiple sclerosis (MS) is very important, since it allows early treatment initiation, which reduces the activity of the disease. The present study aimed to focus a light on the contribution of interlukin-35 (IL-35) and its relation to some hormones such as testosterone, progesterone, and prolactin (PRL) in the pathogenesis of multiple sclerosis. Twenty two enrollers (samples) attended from Teaching hospital of Baghdad were divided into two groups. Ten enrollers were described as healthy subject as control group as group 1 (G1) in range ages (20-30) years. Twelve male patients as group 2 (2) have been relapsing remitting multiple sclerosis (RRMS) matched in age with group 1 (G1).